Menjadi Guru Profesional: Sekadar Profesi atau Panggilan Hati - Iqbal Farabi Sufi, M; wahidah, wahidah; Wiandari, Fadhillah (Mulya Literasi Publishing, 2024)
One way for teachers to be total in teaching and educating is to improve their welfare in terms of income. But also, teachers must always improve their knowledge and abilities to become professional educators so that they have a real influence on students in applying the results of learning in their daily lives. This research aims to find out the quality standards, professionalism, and efforts to improve teacher professionalism in teaching. The type of research used is a literature study with a qualitative descriptive approach. The results show that the government has made efforts to improve teacher professionalism. Among other things, teachers are required to have a minimum education of S-1, participate in teacher work deliberation forums, and provide teacher certification. But in fact, some teachers do not fulfill their calling in educating and are more material-oriented. The teaching profession must be based on a calling to achieve the goals of national education. At the very least, teachers must be qualified and professional in their fields to be exemplary and quality teachers.